EFL: REVISITING ELT PRACTICES IN INDONESIA - Jayanti, Fernandita Gusweni; Norahmi, Maida (Journal on English as a Foreign Language (JEFL), 2014)
In the last decades, we have witnessed a revolutionary spread of English worldwide. This global spread of English can be attributed to the combination of various historical, political, economic, cultural, and technological factors. This led to the emergence of new varieties of English, multiple linguistic and cultural identities. However, for decades, the Western paradigm of English language teaching has occupied a prestigious position in Asia, including Indonesia. This paradigm neglects the emerging varieties of English. Furthermore, it is important to recognize that language teaching and learning is affected by a host of factors ranging from the macro political and cultural environments of a country or region to the micro perceptions and practices of individual teachers or learners, which calls for different methodologies for different learners or learning situations. This article attempts to discuss briefly the current issues in English language teaching (ELT) in Indonesia from English as lingua franca (ELF) perspectives, particularly by taking a close look at all the local features and limitations in the established theories and practices in ELT in Indonesia.Keywords: English language teaching, contextual, methodology, EFL